2007
DOI: 10.1002/cncr.22830
|View full text |Cite
|
Sign up to set email alerts
|

Effects of presurgical exercise training on cardiorespiratory fitness among patients undergoing thoracic surgery for malignant lung lesions

Abstract: BACKGROUND.To determine the effects of preoperative exercise training on cardiorespiratory fitness in patients undergoing thoracic surgery for malignant lung lesions. METHODS.Using a single-group design, 25 patients with suspected operable lung cancer were provided with structured exercise training until surgical resection.Exercise training consisted of 5 endurance cycle ergometry sessions per week at intensities varying from 60% to 100% of baseline peak oxygen consumption (VO 2peak ). Participants underwent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
231
2
15

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 289 publications
(260 citation statements)
references
References 34 publications
12
231
2
15
Order By: Relevance
“…Results indicated that mean VO 2peak increased by 2.4 mL kg -1 min -1 from baseline to presurgery. Exploratory analyses indicated that presurgical VO 2peak decreased postsurgery, but did not decrease beyond baseline values [43]. Similarly, Bobbio et al [44].…”
Section: Exercise Therapy Prior To Surgical Resectionmentioning
confidence: 88%
“…Results indicated that mean VO 2peak increased by 2.4 mL kg -1 min -1 from baseline to presurgery. Exploratory analyses indicated that presurgical VO 2peak decreased postsurgery, but did not decrease beyond baseline values [43]. Similarly, Bobbio et al [44].…”
Section: Exercise Therapy Prior To Surgical Resectionmentioning
confidence: 88%
“…For radiculopathy patients, PT prior to surgery, in general, has been associated with beneficial effects on postoperative patient outcomes. [19][20][21][22][23][24] In the current study, the difference in baseline functioning, age, and smoking history between those patients receiving PT and those who did not could account for some of the postoperative differences observed. These factors could influence surgical outcomes independently of the use of PT.…”
Section: Discussionmentioning
confidence: 99%
“…14 Even for individuals who have not been chronically engaging in regular exercise, there is evidence to suggest that intensive exercise training interventions in the acute setting before surgery may be beneficial. In a cohort of patients undergoing surgical resection of malignant lung lesions, Jones et al 51 found an improvement in cardiorespiratory fitness (mean VO 2Peak increased by 2.4 ml kg À1 per min) after only 4-6 weeks of presurgical structured exercise training. Several studies investigating cardiac surgery patients have demonstrated that surgical complications are inversely associated with exercise capacity.…”
Section: Surgical Treatmentmentioning
confidence: 99%